PENGARUH LABA BERSIH, PERTUMBUHAN PERUSAHAAN DAN ROI TERHADAP DIVIDEN KAS PADA SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Destia Aktarina; Rahma Kurnia (P3M STIE Mulia Darma Pratama, 2021)
Cash dividend is a dividend that cash payment to shareholders in accordance with the percentage of its shares. Net income is the excess of all revenues for all costs for a given period after deducting the income tax presented in the form of income statement. Net income and cash dividends have a relationship, if net income has increased it can be predicted that the dividend also increases, and conversely the decline of dividend received indicates the condition of the company is not good. Growth of the Company (growth) is the ability of the company to increase the size of asset increase existence, equity, profit and sales. To measure how large the company is growing within a certain period of time. Growth of companies and cash dividends have a relationship in which the company in the growth phase requires very much funding, because a company is pleased to use the company's profit from the use of outside party loans, because of the interest burden and date of time that has been agreed together. Thus the growth of the company affects the cash dividend. Return on investment or ROI is the return on investment that is calculated based on the distribution of revenue generated by the size of the invested capital. Return on Investment (ROI) and cash dividends have a relationship where the greater the ROI shows the company's performance is getting better, because the return of the investment is greater.The research aims to determine the development of net profit, growth of the company and Return on Investment (ROI) on cash dividends and to determine the impact of net profit, company growth and Return on Investment (ROI) on dividends of the food and beverage sub-sectors listed on the Indonesian stock exchange both simultaneously and partially. Locus Research is a sub-sector of food and beverage listed on the Indonesian Stock exchange from 2012-2018 period. Sampling is carried out using purposive sampling with the number of samples used as many as 5 companies in the food and beverage sub-sectors listed on the Indonesia Stock Exchange period 2012-2018. The secondary data source in this study took over from Indonesia Stock Exchange. The research methods used in this study are quantitative approaches. Data analysis techniques use multiple linear regression analyses and classical assumptions. Based on the results of net income, company growth and ROI are influential and significant to the cash dividend simultaneously whereas net profit and company growth are influential and significant to the cash dividend partially and ROI does not affectcash dividends partially.